The Sixteenth Marcel Grossmann Meeting On Recent Developments In Theoretical And Experimental General Relativity, Astrophysics, And Relativistic Field Theories - Proceedings Of The Mg16 Meeting On General Relativity (In 4 Volumes) - Ruffini, Remo; Vereshchagin, Gregory (World Scientific Publishing Company, 2022)
The proceedings of MG16 give a broad view of all aspects of gravitational physics and astrophysics, from mathematical issues to recent observations and experiments. The scientific program of the meeting included 46 plenary presentations, 3 public lectures, 5 round tables and 81 parallel sessions arranged during the intense six-day online meeting. All talks were recorded and are available on the ICRANet YouTube channel at the following link: www.icranet.org/video_mg16.These proceedings are a representative sample of the very many contributions made at the meeting. They contain 383 papers, among which 14 come from the plenary sessions.The material represented in these proceedings cover the following topics: accretion, active galactic nuclei, alternative theories of gravity, black holes (theory, observations and experiments), binaries, boson stars, cosmic microwave background, cosmic strings, dark energy and large scale structure, dark matter, education, exact solutions, early universe, fundamental interactions and stellar evolution, fast transients, gravitational waves, high energy physics, history of relativity, neutron stars, precision tests, quantum gravity, strong fields, and white dwarf; all of them represented by a large number of contributions.The online e-proceedings are published in an open access format.